2013
DOI: 10.5747/ca.2013.v09.n1.a083
|View full text |Cite
|
Sign up to set email alerts
|

Enraizamento De Melaleuca: Influência Da Altura De Coleta Das Estacas E Aplicação De Iba

Abstract: RESUMOMelaleuca alternifolia Cheel é uma planta medicinal de importância econômica. Sua constituição química é bem conhecida, sendo rica em terpinen-4-ol, principal responsável por suas propriedades medicinais. Contudo, esta espécie apresenta entraves à obtenção de mudas de qualidade via sementes, de maneira que a propagação vegetativa pode beneficiar sua comercialização, mantendo as características produtivas e de qualidade do óleo extraído. O presente trabalho objetivou avaliar o enraizamento de estacas de m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
1
10
0
5
Order By: Relevance
“…This indicator can be checked also when considering the fact that, regardless of IBA concentrations, there are higher percentages of live or dead cuttings (Figure 1c,1d) in comparison to the cuttings with calluses. These results have often been observed for other tree species as Melaleuca alternifolia (STUEPP et al, 2013), and shrub, as Calliandra brevipes and C. tweedii (MAYER et al, 2008).…”
Section: Resultssupporting
confidence: 56%
“…This indicator can be checked also when considering the fact that, regardless of IBA concentrations, there are higher percentages of live or dead cuttings (Figure 1c,1d) in comparison to the cuttings with calluses. These results have often been observed for other tree species as Melaleuca alternifolia (STUEPP et al, 2013), and shrub, as Calliandra brevipes and C. tweedii (MAYER et al, 2008).…”
Section: Resultssupporting
confidence: 56%
“…Os baixos valores obtidos para mortalidade podem ser considerados satisfatórios para a espécie. Isso sugere que as condições em que o experimento foi conduzido foram favoráveis para a manutenção da sobrevivência das estacas (STUEPP et al, 2013).…”
Section: Brotações Provenientes De Anelamento E Decepa Coletadas No Vunclassified
“…Zem et al (2015) did not find influence on the rooting process of Drymis brasilienses (Winteracea) given the application of different concentrations of IBA when they were cultivated in the four seasons. Similarly, the effect of different concentrations of IBA was not observed by Stuepp et al (2013) on the propagation of Melaleuca alternifolia. Silva, Antunes, Roveda, Carvalho, and Biasi (2012), reported that in Cerrado species that were not domesticated, great genetic variability was observed in size, color and nutritional reserves.…”
Section: Resultsmentioning
confidence: 88%